p38 and Casein Kinase 2 Mediate Ribonuclease 1 Repression in Inflamed Human Endothelial Cells via Promoter Remodeling Through Nucleosome Remodeling and Deacetylase Complex - Bedenbender, Katrin; Beinborn, Isabell; Vollmeister, Evelyn; Schmeck, Bernd (Frontiers in Cell and Developmental Biology, 2020)
Vascular pathologies, such as thrombosis or atherosclerosis, are leading causes of death worldwide and are strongly associated with the dysfunction of vascular endothelial cells. In this context, the extracellular endonuclease Ribonuclease 1 (RNase1) acts as an essential protective factor in regulation and maintenance of vascular homeostasis. However, long-term inflammation causes strong repression of RNase1 expression, thereby promoting endothelial cell dysfunction. This inflammation-mediated downregulation of RNase1 in human endothelial cells is facilitated via Histone Deacetylase (HDAC) 2, although the underlying molecular mechanisms are still unknown. Here, we report that inhibition of c-Jun N-terminal kinase by small chemical compounds in primary human endothelial cells decreased physiological RNase1 mRNA abundance, while p38 kinase inhibition restored repressed RNase1 expression upon proinflammatory stimulation with TNF-α and poly I:C. Moreover, blocking of the p38 kinase- and HDAC2 associated kinase Casein kinase 2 (CK2) by inhibitor as well as siRNA-knockdown restored RNase1 expression upon inflammation of human endothelial cells. Further downstream, siRNA-knockdown of Chromodomain Helicase DNA Binding Protein (CHD) 3 and 4 of the Nucleosome Remodeling and Deacetylase (NuRD) complex restored RNase1 repression in TNF α treated endothelial cells implicating its role in the HDAC2 containing repressor complex involved in RNase1 repression. Finally, Chromatin Immunoprecipitation in primary human endothelial cells confirmed recruitment of the CHD4-containing NuRD complex and subsequent promoter remodeling via histone deacetylation at the RNASE1 promoter in a p38 dependent manner upon human endothelial cell inflammation. Altogether, our results suggest that endothelial RNase1 repression in chronic vascular inflammation is regulated by a p38 kinase-, CK2-, and NuRD complex-dependent pathway resulting in complex recruitment to the RNASE1 promoter and subsequent promoter remodeling.